Optical gas sensing by micro‐photoluminescence on multiple and single ZnO nanowires. Issue 8 (18th March 2015) - Madel, Manfred; Jakob, Julian; Huber, Florian; Neuschl, Benjamin; Bauer, Sebastian; Xie, Yong; Tischer, Ingo; Thonke, Klaus
Abstract ZnO nanowires with average diameters of 50–200 nm were grown by chemical vapor deposition. Their gas sensing properties were analyzed by micro‐photoluminescence spectroscopy allowing for optical readout. The influence of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2dckcq72" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2</alternatives> atmosphere on the emission intensity was investigated for ZnO nanowires with different metal cover layers and after <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2dckcq8m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2</alternatives> plasma pre‐treatment. Investigations of single ZnO nanowires showed an improved sensitivity towards <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2dckcrk3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2</alternatives>.<inline-graphic xlink:href="ark:/27927/pgj2dckc6nx" content-type="pssa201431688-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Photoresponse of a single ZnO nanowire (inset) to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2dckcrh0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2</alternatives> ambient.